Conductive composite structure and method for producing the same

By dispersing MXene with organic compounds with hydroxyl and carbonyl groups on the surface of the metal substrate and performing heat treatment, the problem of insufficient bending resistance and binding force of the MXene conductive film is solved, and high bending resistance and strong binding conductivity are achieved. Composite structure.

CN114901470BActive Publication Date: 2024-12-17MURATA MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080089834.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-25
Filing Date
2020-12-07
Publication Date
2024-12-17
Estimated Expiration
2040-12-07

AI Technical Summary

Technical Problem

The existing MXene conductive film is prone to cracks when bending, has low bending resistance, and is not fully combined with the metal substrate, making it easy to peel off.

Method used

The MXene is dispersed as a liquid medium using an organic compound having a carbon number of 2 or more and 8 or less of hydroxyl group, carbonyl group or combination of them on the surface of the metal substrate, and a conductive film is formed by heat treatment to ensure the close bond between the MXene and the metal substrate.

Benefits of technology

The bending resistance of the conductive film and its bonding force with the metal substrate are improved, cracks and peeling are prevented, and the density and adhesion strength of the film are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114901470B_ABST
    Figure CN114901470B_ABST
Patent Text Reader

Abstract

The present invention provides a conductive composite structure having high bending resistance and high bonding strength between a conductive film and a metal substrate, wherein the conductive film comprises MXene. The conductive composite structure of the present invention is a conductive composite structure comprising a metal substrate and a conductive film disposed on the surface of the metal substrate, wherein the conductive film comprises a layered material, wherein the layered material comprises one or more layers, wherein the layers comprise a MXene having a formula: m X n (wherein M is at least one metal of Group 3, 4, 5, 6, or 7, X is a carbon atom, a nitrogen atom, or a combination thereof, n is greater than 1 and less than 4, and m is greater than n and less than 5) and a modification or terminal T (T is a hydroxyl group, an oxygen atom, or a combination thereof) present on the surface of the layer body, wherein the surface of the metal substrate and the surface of the layer body are respectively bonded with residues from an organic compound having a hydroxyl group, a carbonyl group, or a combination thereof and having a carbon number of greater than 2 and less than 8.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a conductive composite structure, and more particularly to a conductive composite structure including a metal substrate and a conductive film provided on a surface of the metal substrate, and a method for producing the same. Background Art

[0002] In recent years, MXene has attracted attention as a new material with electrical conductivity. MXene is a type of so-called two-dimensional material, and as described later, is a layered material having a morphology of one or more layers.

[0003] It is known that MXene can be used as an electrode active material for electrochemical capacitors (especially pseudocapacitors) and lithium-ion batteries (for example, refer to Patent Document 1, etc.). Electrodes using MXene as an electrode active material can be made in the form of a conductive film formed by a mixture containing MXene and a binder, and depending on the situation, can be made in the form of a conductive film formed only by MXene. In addition, electrodes using MXene as an electrode active material can also be made by forming such a conductive film on the surface of a collector made of a metal substrate. More specifically, a slurry containing MXene as an electrode active material, a binder, and an organic solvent is prepared, applied to the collector, dried, and pressed, thereby fixing it. (See paragraphs 0020, 0026, 0042, etc. of Patent Document 1.)

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-63171 Summary of the invention

[0007] Problems to be solved by the invention

[0008] The previously known conductive films formed only of MXene are difficult to maintain the shape of the film by relying solely on MXene, and cracks may occur when bent, and there is a disadvantage of low bending resistance. In contrast, although the conductive film formed by a mixture containing MXene and a binder has improved bending resistance, the surface and / or interlayer of the MXene may be hindered by the binder, so it is difficult to obtain sufficiently high bending resistance while fully utilizing the electrical properties of the MXene itself. In addition, according to the previously known method, when a conductive film formed only of MXene or a conductive film formed of a mixture containing MXene and a binder is formed on the surface of a collector made of a metal substrate, the bonding between the conductive film and the metal substrate is not sufficient, and there is a disadvantage of being easy to peel off.

[0009] The object of the present invention is to provide a conductive composite structure having high bending resistance and high bonding strength between a conductive film and a metal substrate, the conductive composite structure comprising a metal substrate and a conductive film disposed on a surface of the metal substrate, wherein the conductive film comprises MXene. A further object of the present invention is to provide a method for producing the conductive composite structure.

[0010] Means for solving problems

[0011] According to one aspect of the present invention, there is provided a conductive composite structure comprising a metal substrate and a conductive film provided on a surface of the metal substrate.

[0012] The conductive film comprises a layered material, wherein the layered material comprises one or more layers,

[0013] The layer comprises a layer body represented by the following formula, and a modification or terminal T (T is a hydroxyl group, an oxygen atom, or a combination thereof) present on the surface of the layer body,

[0014] M m X n

[0015] (wherein, M is at least one metal of Group 3, 4, 5, 6, or 7,

[0016] X is a carbon atom, a nitrogen atom or a combination thereof,

[0017] n is greater than or equal to 1 and less than or equal to 4,

[0018] m is greater than n and less than 5)

[0019] A residue derived from an organic compound having 2 to 8 carbon atoms and having a hydroxyl group, a carbonyl group, or a combination thereof is bonded to the surface of the metal substrate and the surface of the layer body.

[0020] According to another aspect of the present invention, there is provided a method for producing a conductive composite structure comprising a metal substrate and a conductive film disposed on a surface of the metal substrate, the method comprising:

[0021] (a) preparing a dispersion liquid in which a layered material is dispersed in a liquid medium containing an organic compound having 2 to 8 carbon atoms and having a hydroxyl group, a carbonyl group or a combination thereof, wherein the layered material is a layered material including one or more layers,

[0022] The layer includes a layer body represented by the following formula and a modification or terminal T (T is a hydroxyl group, an oxygen atom, or a combination thereof) present on the surface of the layer body:

[0023] M m X n

[0024] (wherein, M is at least one metal of Group 3, 4, 5, 6, or 7,

[0025] X is a carbon atom, a nitrogen atom or a combination thereof,

[0026] n is greater than or equal to 1 and less than or equal to 4,

[0027] m is greater than n and less than 5);

[0028] (b) applying the dispersion to the surface of a metal substrate; and

[0029] (c) subjecting the metal substrate to which the dispersion has been applied to heat treatment.

[0030] Effects of the Invention

[0031] According to the conductive composite structure of the present invention, in the conductive composite structure comprising a metal substrate and a conductive film disposed on the surface of the metal substrate, the conductive film comprises a predetermined layered material (also referred to as "MXene" in this specification), and the surface of the metal substrate and the surface of the layer body of the layered material are respectively bonded with residues derived from an organic compound having a carbon number of 2 or more and 8 or less and having a hydroxyl group, a carbonyl group, or a combination thereof, thereby providing a conductive composite structure having high bending resistance and a high bonding strength between the conductive film and the metal substrate. In addition, according to the method for manufacturing a conductive composite structure of the present invention, a dispersion in which MXene is dispersed in a liquid medium comprising an organic compound having a carbon number of 2 or more and 8 or less and having a hydroxyl group, a carbonyl group, or a combination thereof is used, and the dispersion is applied to the surface of the metal substrate and then subjected to heat treatment, thereby manufacturing a conductive composite structure having high bending resistance and a high bonding strength between the conductive film and the metal substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a schematic cross-sectional view showing a conductive composite structure according to one embodiment of the present invention.

[0033] Figure 2 This is a schematic cross-sectional view showing a layered material, MXene, which can be used in an electrically conductive composite structure according to one embodiment of the present invention.

[0034] Figure 3 The figures show the evaluation results of the conductive composite structure produced in Example 1 of the present invention, wherein (a) shows the result of the mandrel winding test, (b) shows the result of the acetone immersion test, and (c) shows the result of the tape peeling test.

[0035] Figure 4The figures show the evaluation results of the conductive composite structure produced in Example 2 of the present invention, (a) shows the result of the mandrel winding test, (b) shows the result of the acetone immersion test, and (c) shows the result of the tape peeling test.

[0036] Figure 5 The figures show the evaluation results of the conductive composite structure produced in Example 3 of the present invention, (a) shows the result of the mandrel winding test, (b) shows the result of the acetone immersion test, and (c) shows the result of the tape peeling test.

[0037] Figure 6 The figures show the evaluation results of the conductive composite structure produced in Example 4 of the present invention, (a) shows the result of the mandrel winding test, (b) shows the result of the acetone immersion test, and (c) shows the result of the tape peeling test.

[0038] Figure 7 The figures show the evaluation results of the conductive composite structure produced in Comparative Example 1, (a) shows the result of the mandrel winding test, (b) shows the result of the acetone immersion test, and (c) shows the result of the tape peeling test. DETAILED DESCRIPTION

[0039] Hereinafter, a conductive composite structure according to one embodiment of the present invention will be described in detail with reference to a method for producing the conductive composite structure. However, the present invention is not limited to this embodiment.

[0040] Reference Figure 1 The conductive composite structure 20 of the present embodiment includes a metal substrate 11 and a conductive film 13 provided on the surface of the metal substrate 11 .

[0041] The method for manufacturing the conductive composite structure 20 of this embodiment includes:

[0042] (a) preparing a dispersion in which a predetermined layered material is dispersed in a liquid medium containing an organic compound having 2 or more and 8 carbon atoms and having a hydroxyl group, a carbonyl group, or a combination thereof (in other words, a hydroxyl group and / or an oxygen atom);

[0043] (b) applying the dispersion to the surface of a metal substrate; and

[0044] (c) subjecting the metal substrate to which the dispersion has been applied to heat treatment.

[0045] Process (a)

[0046] First, a predetermined layered material is prepared. The predetermined layered material that can be used in this embodiment is MXene, which is defined as follows:

[0047] The present invention is a layered material comprising one or more layers, wherein the layer is a layered material (which can be understood as a layered compound, also represented by “M”) comprising a layer body represented by the following formula (the layer body may have a lattice in which each X is located in an octahedral array of M) and a modified or terminal T (T is a hydroxyl group, an oxygen atom, or a combination thereof (in other words, a hydroxyl group and / or an oxygen atom), and may also be a fluorine atom and / or a hydrogen atom) present on the surface of the layer body (more specifically, at least one of the two surfaces of the layer body facing each other). m X n T s ", s is an arbitrary number. In the past, x was sometimes used instead of s):

[0048] M m X n

[0049] (wherein, M is at least one metal of Group 3, 4, 5, 6, or 7, and may include at least one selected from the so-called early transition metals, such as Sc, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, and Mn,

[0050] X is a carbon atom, a nitrogen atom or a combination thereof,

[0051] n is greater than or equal to 1 and less than or equal to 4,

[0052] m is greater than n and less than 5).

[0053] Typically, n may be 1, 2, 3 or 4, but is not limited thereto.

[0054] In this embodiment, MXene may have hydroxyl groups and / or oxygen atoms in the form of modified or terminal T, preferably both hydroxyl groups and oxygen atoms. Hydroxyl groups and / or oxygen atoms present in the form of modified or terminal T in MXene contribute to the reaction described below.

[0055] In the above formula of MXene, M is preferably at least one selected from Ti, Zr, Hf, V, Nb, Ta, Cr and Mo.

[0056] The MXene can be synthesized by selectively etching (removing and optionally layer-separating) A atoms (and optionally a portion of M atoms) from the MAX phase. The MAX phase is represented by the following formula:

[0057] M m AX n

[0058] (wherein, M, X, n and m are as described above, A is at least one element of Groups 12, 13, 14, 15 and 16, usually an element of Group A, typically an element of Groups IIIA and IVA, and more specifically may include at least one selected from Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, As, S and Cd, preferably Al),

[0059] The MAX phase has a layer formed by A atoms located at M m X n The MAX phase has a crystal structure represented by two layers (which may have a lattice in which each X is located in an octahedral array of M). In the case of m=n-+-1, the MAX phase has a repeating unit in which one layer of X atoms is arranged between each layer of n+1 layers of M atoms (these layers are collectively referred to as "M m X n The A-atom layer (and optionally a part of the M atoms) is removed by selectively etching (removing and optionally layer-separating) the A atoms (and optionally a part of the M atoms) from the MAX phase, and the exposed M atoms are formed. m X n The surface of the layer is modified by terminating the surface with hydroxyl groups and / or oxygen atoms (or fluorine atoms and / or hydrogen atoms, etc., as appropriate) present in an etching solution (usually an aqueous solution containing fluorine acid is used, but it is not limited thereto). - The etching solution may be implemented, for example, a method using a mixture of lithium fluoride and hydrochloric acid, a method using hydrofluoric acid, etc. Thereafter, any suitable post-treatment (such as ultrasonic treatment, hand-cranking or automatic shaker, etc.) may be appropriately used to promote the layer separation of MXene (stratification, separation of multilayer MXene into single-layer MXene and / or few-layer MXene). It should be noted that ultrasonic treatment may damage MXene particles due to excessive shear force. Therefore, when it is desired to obtain a two-dimensional MXene with a larger aspect ratio (preferably a single-layer MXene and / or a few-layer MXene), it is preferred to use a hand-cranking or automatic shaker to impart appropriate shear force.

[0060] MXene is known to have the formula expressed as follows: m X n of layered materials.

[0061] Sc2C, Ti2C, Ti2N, Zr2C, Zr2N, Hf2C, Hf2N, V2C, V2N, Nb2C, Ta2C, Cr2C, Cr2N, Mo2C, Mo 1.3C.Cr 1.3 C, (Ti, V)2C, (Ti, Nb)2C, W2C, W 1.3 C, Mo2N, Nb 1.3 C.Mo 1.3 Y 0.6 C (In the above formula, "1.3" and "0.6" refer to approximately 1.3 (= 4 / 3) and approximately 0.6 (= 2 / 3), respectively.)

[0062] Ti3C2, Ti3N2, Ti3(CN), Zr3C2, (Ti, V)3C2, (Ti2Nb)C2, (Ti2Ta)C2, (Ti2Mn)C2, Hf3C2, (Hf2V)C2, (Hf2Mn)C2, (V2Ti)C2, (Cr2Ti)C2, (Cr2V)C 2. (Cr2Nb)C2, (Cr2Ta)C2, (Mo2Sc)C2, (Mo2Ti)C2, (Mo2Zr)C2, (Mo2Hf)C2, (Mo2V)C2, (Mo2Nb)C2, (Mo2Ta)C2, (W2Ti)C2, (W2Zr)C2, (W2Hf)C2,

[0063] Ti4N3, V4C3, Nb4C3, Ta4C3, (Ti, Nb) 4C3, (Nb, Zr) 4C3, (Ti2Nb2)C3, (Ti2Ta2)C3, (V2Ti2)C3, (V2Nb2)C3, (V2Ta2)C3, (Nb2Ta2)C3, (Cr2Ti2)C3, (Cr 2V2)C3, (Cr2Nb2)C3, (Cr2Ta2)C3, (Mo2Ti2)C3, (Mo2Zr2)C3, (Mo2Hf2)C3, (Mo2V2)C3, (Mo2Nb2)C3, (Mo2Ta2)C3, (W2Ti2)C3, (W2Zr2)C3, (W2Hf2)C3

[0064] In a typical case, in the above formula, M can be titanium or vanadium, and X can be a carbon atom or a nitrogen atom. For example, MAX phase is Ti3AlC2, and MXene is Ti3C2T s .

[0065] It should be noted that in the present invention, MXene may contain a relatively small amount of residual A atoms, for example, 10% by mass or less of A atoms relative to the original A atoms. The residual amount of A atoms may preferably be 8% by mass or less, more preferably 6% by mass or less. However, even if the residual amount of A atoms is greater than 10% by mass, there may sometimes be no problem depending on the purpose and use conditions of the conductive composite structure.

[0066] like Figure 2As schematically shown in FIG. 1 , the MXene 10 synthesized as described above may be a layered material including one or more MXene layers 7a, 7b, and 7c (three layers are shown in the figure, but it is not limited thereto). More specifically, the MXene layers 7a, 7b, and 7c have a MXene structure. m X n The layer body represented by m X n MXene layers 7a, 7b, 7c may also be represented by “MXene layers” 1a, 1b, 1c, and modifications or terminations T 3a, 5a, 3b, 5b, 3c, 5c present on the surfaces of the layer bodies 1a, 1b, 1c (more specifically, at least one of the two surfaces facing each other in each layer). m X n T s ", s is an arbitrary number. MXene10 may be a layered material in which the MXene layers are separated and exist as one layer (single-layer structure, so-called single-layer MXene), or a stacked body in which a plurality of MXene layers are stacked separately from each other (multi-layer structure, so-called multi-layer MXene), or a mixture thereof. MXene may be particles (also referred to as powder or flakes) that are aggregates formed by single-layer MXene and / or multi-layer MXene. In the case of multi-layer MXene, two adjacent MXene layers (for example, 7a and 7b, 7b and 7c) are not necessarily completely separated, but may be partially in contact.

[0067] Although not limiting the present embodiment, the thickness of each layer of MXene (corresponding to the above-mentioned MXene layers 7a, 7b, 7c) is, for example, greater than 0.8 nm and less than 5 nm, particularly greater than 0.8 nm and less than 3 nm (may vary mainly depending on the number of M atomic layers contained in each layer), and the maximum size in the plane parallel to the layer (two-dimensional sheet surface) is, for example, greater than 0.1 μm and less than 200 μm, particularly greater than 1 μm and less than 40 μm.

[0068] In the case of a stacked body (multilayer MXene), for each stacked body, the interlayer distance (or gap size, Figure 2 The maximum size of the layer (represented by Δd in the figure) is, for example, greater than 0.8 nm and less than 10 nm, particularly greater than 0.8 nm and less than 5 nm, more particularly about 1 nm, and the maximum size in the plane perpendicular to the stacking direction (two-dimensional sheet surface) is, for example, greater than 0.1 μm and less than 100 μm, particularly greater than 1 μm and less than 20 μm.

[0069] In addition, when MXene is a stack (multilayer MXene), for each stack, the total number of layers can be 2 or more, for example, 50 or more and 100,000 or less, especially 1,000 or more and 20,000 or less, and the thickness in the stacking direction is, for example, 0.1 μm or more and 200 μm or less, especially 1 μm or more and 40 μm or less.

[0070] In the case where MXene is a laminate (multilayer MXene), it may be a MXene with a small number of layers. The term "small number of layers" means, for example, that the number of layers of MXene is 6 or less. In addition, the thickness of the stacking direction of the multilayer MXene with a small number of layers is preferably 10 nm or less. In this specification, the "multilayer MXene with a small number of layers" (multilayer MXene in a narrow sense) is also referred to as "few-layer MXene".

[0071] In this embodiment, MXene 10 may be particles (also referred to as nanosheets) of which most of the particles are formed by single-layer MXene 10a and / or few-layer MXene. In other words, the proportion of particles (single-layer MXene and / or few-layer MXene) having a thickness of 10 nm or less in the stacking direction among the entire MXene particles may be 50% by volume or more.

[0072] It should be noted that the above-mentioned dimensions are obtained as the number average dimensions (e.g., the number average of at least 40 dimensions) based on photographs taken with a scanning electron microscope (SEM), a transmission electron microscope (TEM), or an atomic force microscope (AFM), or as the distance in actual space calculated from the position in the reciprocal lattice space of the (002) plane measured by the X-ray diffraction (XRD) method.

[0073] Separately, a liquid medium containing an organic compound having 2 to 8 carbon atoms and having a hydroxyl group and / or a carbonyl group (hereinafter also simply referred to as a "reactive organic compound") is prepared.

[0074] The reactive organic compound has a hydroxyl group and / or a carbonyl group, and typically may have any one of a hydroxyl group and a carbonyl group. The hydroxyl group and / or carbonyl group of the reactive organic compound contributes to the reaction described below.

[0075] The carbon number of the reactive organic compound is 2 or more and 8 or less, preferably 3 or more and / or 7 or less. By making the carbon number 2 or more, preferably 3 or more, the aggregation of MXene in the dispersion (before the heat treatment described later) can be prevented. By making the carbon number 8 or less, preferably 7 or less, when the MXene is a laminate (multilayer MXene), it can appropriately penetrate between the layers of the laminate.

[0076] The reactive organic compound may be an alcohol or ketone having a carbon number of 2 to 8. More specifically, the reactive organic compound may be at least one selected from isopropyl alcohol, N-methylpyrrolidone and methyl ethyl ketone, and may be any one of them or a mixture of any two or more thereof.

[0077] The liquid medium is preferably formed of a reactive organic compound, but may also contain other organic compounds in a small amount (for example, 30% by mass or less, preferably 20% by mass or less, based on the overall basis) in addition to the reactive organic compound. The liquid medium may contain water in a very small amount (for example, 30% by mass or less, preferably 20% by mass or less, based on the overall basis) depending on the reactive organic compound used.

[0078] A dispersion (also referred to as a suspension or slurry) in which the MXene is dispersed in the liquid medium is prepared. The dispersion method is not particularly limited, and typically may be stirring (shear mixer, pot mill, etc.), ultrasonic treatment, oscillation, etc.

[0079] In the dispersion, the reactive organic compound can contact the surface of the MXene, and when the MXene is a laminate (multilayer MXene), can contact the outermost surface of the laminate, and can infiltrate between the layers of the laminate.

[0080] The content ratio of MXene in the dispersion is not particularly limited, and may be, for example, 20 to 95% by mass.

[0081] Process (b)

[0082] First, a metal substrate 11 is prepared. The metal substrate 11 may be a conductive member based on one or more metals. The so-called "metal-based conductive member" refers to a member that is conductive as a whole and has a metal content (a total content of these metals when two or more metals are included) of 80% by weight or more, for example, 90% by weight or more, preferably 95% by weight or more. Other conductive substances other than metals that can constitute the metal substrate 11 include, for example, carbon.

[0083] The metal substrate 11 may have hydroxyl groups, oxygen atoms, or a combination thereof (in other words, hydroxyl groups and / or oxygen atoms) on its outermost surface, and preferably may have both hydroxyl groups and oxygen atoms. The hydroxyl groups and / or oxygen atoms present on the outermost surface of the metal substrate 11 contribute to the reaction described below.

[0084] The metal substrate 11 may have a sheet-like shape in a typical case. The so-called "sheet-like" means a shape having two planes facing each other and a small distance (thickness) between these planes, as generally understood, and may be called a film or foil in addition to a sheet. However, the metal substrate 11 is not limited thereto and may have any suitable shape.

[0085] It should be noted that even if the metal substrate 11 is a metal member, strictly speaking, it is not entirely composed of metal atoms. The hydroxyl groups and / or oxygen atoms present on the outermost surface of the metal substrate 11 may be hydroxyl groups and / or oxygen atoms present on the outermost surface of a metal oxide film (more specifically, an amorphous metal oxide film, i.e., a so-called passivation film) present on the surface portion of the metal substrate 11.

[0086] The metal substrate 11 can be an aluminum substrate, a copper substrate or a stainless steel substrate (in other words, a conductive component based on aluminum, copper or stainless steel), more specifically, an aluminum component, a copper component or a stainless steel component. The aluminum component has a film of aluminum oxide (which can be amorphous) formed on its surface portion, and the outermost surface of the aluminum oxide film has hydroxyl groups and / or oxygen atoms, usually both hydroxyl groups and oxygen atoms. The copper component has a film of copper oxide (which can be amorphous) formed on its surface portion, and the outermost surface of the copper oxide film has hydroxyl groups and / or oxygen atoms, usually both hydroxyl groups and oxygen atoms. Stainless steel is steel with a carbon content of less than 1.2% by mass and a chromium content of more than 10.5% by mass, and may contain additional metals such as nickel as appropriate. Stainless steel may be, for example, SUS304, SUS316, SUS430, etc. The stainless steel member has a film of iron oxide and chromium oxide (which may be amorphous) formed on its surface. The outermost surface of the iron oxide-chromium oxide film has hydroxyl groups and / or oxygen atoms, and usually has both hydroxyl groups and oxygen atoms.

[0087] However, the metal substrate 11 (e.g., an aluminum substrate, a copper substrate, or a stainless steel substrate) may have other conductive substances other than metal as described above. In a representative case, a carbon coating may be formed on a metal member (e.g., an aluminum member, a copper member, or a stainless steel member). Carbon has hydroxyl groups and / or oxygen atoms on its outermost surface, and usually has both hydroxyl groups and oxygen atoms, unless a special treatment such as a hydrophobic treatment is performed.

[0088] The size of the metal substrate 11 is not particularly limited and can be appropriately selected according to the application of the conductive composite structure 20. The thickness of the metal substrate 11 is preferably a thickness that allows bending, but this is not essential in applications that do not require high bending resistance.

[0089] Thereafter, the dispersion prepared in the above step (a) is applied to (more specifically, coated on) the surface of the metal substrate 11. The application method is not particularly limited, and for example, blade coating, knife coating, bar coating, screen printing, die coating, die coating, roller coating, dip coating, spray coating, spin coating, etc. can be used.

[0090] The thickness of the dispersion applied to the surface of the metal substrate 11 may vary depending on the composition of the dispersion and the desired thickness of the conductive film 13 .

[0091] Process (c)

[0092] The metal substrate 11 to which the dispersion liquid has been applied in the above step (b) is subjected to heat treatment.

[0093] By heat treatment, the reactive organic compound can react with the metal substrate 11 and can also react with the MXene 10. More specifically, the following reaction can be performed.

[0094] In the case where the reactive organic compound has a hydroxyl group, the hydroxyl group of the reactive organic compound can react with the oxygen atom present on the outermost surface of the metal substrate 11 to form a bond therebetween. In addition, the hydroxyl group of the reactive organic compound can react with the oxygen atom present in the form of a modification or terminal T on the surface of the layer body 1a, 1b, 1c of the MXene10 to form a bond therebetween. More specifically, these reactions can be reactions in which hydrogen bonds are formed between the hydrogen atoms of the hydroxyl group of the reactive organic compound and the oxygen atoms of the metal substrate 11 / MXene10, but are not limited thereto. For example, reactions in which hydrogen atoms are separated from the reactive organic compound may also be performed.

[0095] In the case where the reactive organic compound has a carbonyl group, the carbonyl group of the reactive organic compound can react with the hydroxyl group present on the outermost surface of the metal substrate 11 to form a bond therebetween. In addition, the carbonyl group of the reactive organic compound can react with the hydroxyl group present in the form of modification or terminal T on the surface of the layer body 1a, 1b, 1c of MXene10 to form a bond therebetween. More specifically, these reactions can be reactions in which hydrogen bonds are formed between the oxygen atom of the carbonyl group of the reactive organic compound and the hydrogen atom of the hydroxyl group of the metal substrate 11 / MXene10, but are not limited thereto. For example, reactions in which hydrogen atoms are separated from the reactive organic compound may also be involved.

[0096] The present invention is not bound by any theory, but the reaction mechanism can be understood as schematically shown below. It should be noted that, hereinafter, as a case where the reactive organic compound has a hydroxyl group, the case where isopropyl alcohol reacts with MXene and reacts with a copper component is exemplified, and as a case where the reactive organic compound has a carbonyl group, the case where N-methylpyrrolidone reacts with MXene and reacts with an aluminum component, and the case where methyl ethyl ketone reacts with an aluminum component are exemplified, but other cases can also be understood in the same way.

[0097] · When the reactive organic compound has a hydroxyl group

[0098] [Chemistry 1]

[0099]

[0100] [Chemistry 2]

[0101]

[0102] · When the reactive organic compound has a carbonyl group

[0103] [Chemistry 3]

[0104]

[0105] [Chemistry 4]

[0106]

[0107] [Chemistry 5]

[0108]

[0109] In addition, the unreacted reactive organic compound can be evaporated and removed by heat treatment.

[0110] During the heat treatment, the reactive organic compound reacts and is evaporated and removed, thereby making it possible to closely aggregate the MXene (whether a single-layer MXene or a multi-layer MXene).

[0111] The heat treatment conditions may vary depending on the reactive organic compound used. The heat treatment temperature may be, for example, 70°C or more and 200°C or less, preferably 80°C or more and 180°C or less. The heat treatment time may be appropriately set, for example, 0.5 hours or more and 24 hours or less. The heat treatment atmosphere may be a reduced pressure (or vacuum) atmosphere, an air atmosphere, a nitrogen atmosphere, or the like.

[0112] As a result of the heat treatment, a conductive film 13 derived from the dispersion is formed on the surface of the metal substrate 11, thereby producing a conductive composite structure 20 of the present embodiment (see Figure 1). It should be noted that the method for manufacturing the conductive composite structure 20 of the present embodiment may also implement any appropriate subsequent process after the heat treatment in step (c). The subsequent process may be a process of cutting (e.g., punching, etc.) the conductive composite structure 20 into a desired shape, and / or a process of pressing the conductive composite structure 20, etc.

[0113] In the conductive composite structure 20 of the present embodiment, the surface of the metal substrate 11 is bonded with a residue from a reactive organic compound, and the surface of the layer bodies 1a, 1b, and 1c of the MXene (in other words, the surface and / or between the layers of the MXene) is bonded with a residue from a reactive organic compound. The so-called "residue from a reactive organic compound" refers to the residue of the reactive organic compound after the above-mentioned heat treatment. For example, compared with the chemical formula of the original reactive organic compound, the "residue from a reactive organic compound" can be a substance represented by the same chemical formula except for the hydrogen bond forming part, or a substance represented by a chemical formula that has changed due to the separation of hydrogen atoms, etc. It should be noted that in the conductive composite structure 20 of the present embodiment, it should be noted that unreacted hydroxyl groups and / or oxygen atoms remain on the surface of the layer bodies 1a, 1b, and 1c of the MXene in the form of modified or terminal T.

[0114] In addition, in the conductive composite structure 20 of the present embodiment, since the unreacted reactive organic compound is evaporated and removed, the conductive film 13 can be regarded as a dry film.

[0115] In addition, in the conductive composite structure 20 of the present embodiment, the conductive film 13 includes MXene and is provided on the surface of the metal substrate 11 without including a binder (binder-free). Unless otherwise specified, the description of the manufacturing method of the present embodiment can be applied to MXene and the metal substrate in the conductive composite structure 20 in the same manner.

[0116] According to the present embodiment, a conductive composite structure 20 having high bending resistance (particularly softness (flexibility)) and high bonding strength between the conductive film 11 and the metal substrate 13 (particularly chemical stability to organic solvents, peeling strength, etc.) can be manufactured. More specifically, even if the conductive composite structure 20 is bent, cracks are not easily generated in the conductive film 13, and even if the conductive composite structure 20 is immersed in an organic solvent or subjected to a tape peeling test, the conductive film 13 is not easily peeled off from the metal substrate 11. The present invention is not limited to any theory, but the reason why high bending resistance can be obtained in the conductive composite structure 20 is understood to be that the residual part derived from the reactive organic compound exists on the surface and / or between the layers of MXene, thereby making the conductive film 13 higher in density of MXene than the conventionally known conductive film formed only of MXene, and the adhesion strength between MXene (single-layer MXene and / or multi-layer MXene) is increased, and the strength, shapeability and flexibility of the conductive film itself (even without a binder) are also improved. In addition, the reason why high bonding strength can be obtained between the conductive film 13 and the metal substrate 11 can be understood to be because there are remnants from reactive organic compounds on both the surface of MXene and the surface of the metal substrate, and thus the remnants from reactive organic compounds act like an adhesive between the conductive film 13 and the metal substrate 11.

[0117] The conductive composite structure 20 of the present embodiment can be used in any appropriate application. The conductive composite structure 20 of the present embodiment has a high density of MXene in the conductive film 13 and can achieve the desired electrical properties in a smaller size. Therefore, it can be preferably used in the case where the conductive composite structure 20 is required to be miniaturized, and then the product assembled with it is required to be miniaturized. In addition, the conductive composite structure 20 of the present embodiment can be preferably used in the case where the conductive composite structure 20 is required to withstand bending and stretching during the use of the final product assembled with it by the user and / or during the manufacturing process before being assembled into the final product.

[0118] It is particularly preferred that the conductive composite structure 20 of this embodiment can be used as an electrode. When the conductive composite structure 20 is used as an electrode, the MXene of the conductive film 13 acts as an electrode active material (a material that transfers electrons to and from electrolyte ions in an electrolyte solution), and the metal substrate 11 acts as a current collector.

[0119] The electrode is not particularly limited, and may be, for example, a capacitor electrode, a battery electrode, a bioelectrode, a sensor electrode, an antenna electrode, etc. By using the conductive composite structure 20 of this embodiment, a large-capacity capacitor and battery, a low-impedance bioelectrode, a highly sensitive sensor and antenna can be obtained even with a smaller volume (device occupied volume).

[0120] The capacitor may be an electrochemical capacitor. An electrochemical capacitor is a capacitor that utilizes the capacitance exhibited by the physicochemical reaction between an electrode (electrode active material) and ions (electrolyte ions) in an electrolyte, and can be used as a device for storing electrical energy (electricity storage device). A battery may be a chemical battery that can be repeatedly charged and discharged. The battery may be, for example, a lithium ion battery, a magnesium ion battery, a lithium sulfur battery, a sodium ion battery, etc., but is not limited thereto. In the manufacturing process of capacitors and batteries, the electrodes may be required to have flexibility that can withstand bending and stretching. In addition, the electrodes may be bent and configured in the capacitor and battery. In this application, the conductive composite structure 20 of this embodiment can be appropriately used as an electrode.

[0121] The bioelectrode is an electrode for obtaining biological signals. The bioelectrode may be, for example, an electrode for measuring EEG (electroencephalogram), ECG (electrocardiogram), EMG (electromyogram), or EIT (electrical impedance tomography), but is not limited thereto. The bioelectrode can be attached to a living thing (especially the skin) for use, and is required to have the flexibility to withstand flexion and extension without peeling off from the skin even if the skin stretches and contracts. In this application, the conductive composite structure 20 of this embodiment can be appropriately used as an electrode.

[0122] The sensor electrode is an electrode used to detect the substance, state, abnormality, etc. of the target. The sensor may be, for example, a gas sensor, a biosensor (a chemical sensor that utilizes a molecular recognition mechanism of biological origin), etc., but is not limited to them. By using the conductive composite structure 20 of this embodiment as a sensor electrode, a sensor electrode having a high bonding strength with a metal substrate and being overall soft can be provided.

[0123] The antenna electrode is an electrode for radiating electromagnetic waves into space and / or receiving electromagnetic waves in space. By using the conductive composite structure 20 of this embodiment as an antenna electrode, an antenna electrode having high bonding strength with a metal substrate and being overall flexible can be provided.

[0124] The above is a detailed description of the conductive composite structure of one embodiment of the present invention through its manufacturing method, but various changes can be made. It should be noted that the conductive composite structure of the present invention can also be manufactured using a method different from the manufacturing method of the above-mentioned embodiment. In addition, it should be noted that the manufacturing method of the conductive composite structure of the present invention is not limited to the manufacturing method of the conductive composite structure of the above-mentioned embodiment.

[0125] Example

[0126] (Example 1)

[0127] This embodiment relates to an example of producing a conductive composite structure using isopropyl alcohol (IPA) as a reactive organic compound and copper foil as a metal substrate.

[0128] Preparation of MXene powder

[0129] Ti3AlC2 particles were prepared as MAX particles using a known method. 1 g of the Ti3AlC2 particles (powder) were weighed, added to 10 mL of 9 mol / L hydrochloric acid together with 1 g of LiF and stirred at 35 ° C with a stirrer for 24 hours to obtain a solid-liquid mixture (suspension) containing solid components from the Ti3AlC2 powder. The solid-liquid mixture was repeatedly washed with pure water and separated and removed by decantation using a centrifuge (cleaning was applied again to the remaining sediment after the supernatant was removed) for about 10 times, and pure water was added to the sediment to obtain a MXene slurry.

[0130] The obtained MXene slurry was freeze-dried, and the agglomerated dry powder was crushed using a controlled tube mill (manufactured by IKA). Thus, Ti3C2T3O4 as MXene powder was obtained. s powder.

[0131] Preparation of dispersion

[0132] The MXene powder (Ti3C2T s Powder) and isopropyl alcohol (IPA) were stirred with a thin film rotary high-speed stirrer (40-L type, manufactured by Prymix Co., Ltd.) at a ratio of 30 mass % (on a total basis) of MXene. Stirring was repeated while cooling to 20° C. with ice water each time stirring until a substantially uniform MXene-IPA dispersion was obtained.

[0133] ·Coating of dispersion onto metal substrate

[0134] The MXene-IPA dispersion prepared above was coated on the upper surface of a copper foil (manufactured by THANK METAL Co., Ltd., thickness 10 μm) as a metal substrate using a tabletop coater (manufactured by Tester Industry Co., Ltd., PI-1210 automatic coating device). It should be noted that the tabletop coater used a coater equipped with a variable scraper (manufactured by YOSHIIMITSU Seiki Co., Ltd., BAKER-type coater YBA-3 type) with a gap of 127 μm.

[0135] Heat treatment

[0136] The copper foil coated with the MXene-IPA dispersion as described above was subjected to heat treatment at 120°C for 3 hours in a vacuum oven (ETTAS vacuum dryer AVO-310SB manufactured by ASONE Co., Ltd.) in a vacuum (vacuum degree 0.1 kPa). Thus, a structure having a MXene dry film (hereinafter referred to as "IPA-MXene film") from the IPA dispersion formed on the upper surface of the copper foil as a conductive film was obtained.

[0137] ·suppress

[0138] Thereafter, the structure obtained above was pressed using a roll press at a line pressure of 0.6 kN / cm and a conveying speed of 0.3 m / min.

[0139] In this way, the conductive composite structure of Example 1 was obtained.

[0140] ·evaluate

[0141] The conductive composite structure of Example 1 produced above was subjected to a mandrel winding test, an acetone immersion test, and a tape peeling test and evaluated.

[0142] In the mandrel winding test, the conductive composite structure was wound around an aluminum round bar having a diameter of 4 mm for about 2 turns, and the state was maintained to visually check for the presence of cracks and peeling.

[0143] As a result, if Figure 3 As shown in (a), no cracks in the IPA-MXene film and no peeling of the IPA-MXene film from the copper foil were observed.

[0144] In the acetone immersion test, the conductive composite structure was cut to obtain a 1 cm square test piece, and the test piece was immersed in acetone, which is an organic solvent, at room temperature for 1 minute, and the presence or absence of peeling was visually confirmed.

[0145] As a result, if Figure 3 As shown in (b), the IPA-MXene film maintained its original shape, and no peeling between the IPA-MXene film and the copper foil was observed.

[0146] In the tape peeling test, a transparent adhesive tape (manufactured by Nichiban Co., Ltd., "Cellotape" (registered trademark)) was adhered to a portion of the upper surface of the IPA-MXene film of the conductive composite structure, and then peeled off to visually confirm whether there was peeling caused by the tape (transfer to the adhesive surface of the tape).

[0147] As a result, if Figure 3 As shown in (c), in the case of the IPA-MXene film, only about 5% of the total area in the attached region was sparsely peeled off from the copper foil by the tape.

[0148] (Example 2)

[0149] This embodiment relates to an example of using isopropyl alcohol (IPA) as a reactive organic compound and aluminum foil as a metal substrate to produce a conductive composite structure. It should be noted that, unless otherwise specified, the same apparatus as in Example 1 is used, and the same production conditions and evaluation methods are applied (the same applies to the following embodiments and comparative examples).

[0150] Preparation of MXene powder

[0151] The MXene slurry obtained in the same manner as in Example 1 was freeze-dried, and the agglomerated dry powder was pulverized using a planetary ball mill. s The powder is used as MXene powder.

[0152] Preparation of dispersion

[0153] The MXene powder (Ti3C2T s 5.8 g of MXene-IPA powder) and 13.6 g of isopropyl alcohol (IPA) were placed in a glass container, and the glass container containing the mixture was immersed in an ultrasonic bath filled with water and subjected to ultrasonic treatment for 1 hour. The ultrasonic treatment was performed until a substantially uniform MXene-IPA dispersion was obtained.

[0154] ·Coating of dispersion onto metal substrate

[0155] The MXene-IPA dispersion prepared above was applied to the upper surface of an aluminum foil (manufactured by THANK METAL CO., LTD., thickness 10 μm) as a metal substrate using a table-top coater.

[0156] Heat treatment

[0157] The aluminum foil coated with the MXene-IPA dispersion was preheated on a hot plate (100°C, 15 minutes), and then heat treated at 120°C for 3 hours in a vacuum oven (vacuum degree 0.1 kPa). Thus, a structure having a MXene dry film (hereinafter referred to as "IPA-MXene film") from the IPA dispersion formed on the upper surface of the aluminum foil as a conductive film was obtained.

[0158] ·suppress

[0159] Thereafter, the structure obtained above was pressed using a roll press at a line pressure of 4.4 kN / cm and a conveying speed of 0.3 m / min.

[0160] In this way, the conductive composite structure of Example 2 was obtained.

[0161] ·evaluate

[0162] The conductive composite structure of Example 2 prepared above was subjected to the same winding test, acetone immersion test and tape peeling test as in Example 1 and evaluated. The results of the winding test are shown in FIG. Figure 4 As shown in (a), no cracks in the IPA-MXene film and no peeling of the IPA-MXene film from the aluminum foil were observed. Figure 4 As shown in (b), the IPA-MXene film maintained its original shape, and no peeling between the IPA-MXene film and the aluminum foil was observed. Figure 4 As shown in (c), the IPA-MXene film was not peeled off from the aluminum foil by the tape at all. Example 2 showed the best result among Examples 1-4.

[0163] (Example 3)

[0164] This embodiment relates to an example of producing a conductive composite structure using N-methylpyrrolidone (NMP) as a reactive organic compound and aluminum foil as a metal substrate.

[0165] Preparation of MXene powder

[0166] The MXene slurry obtained in the same manner as in Example 1 was freeze-dried, and the agglomerated dry powder was pulverized using a controlled tube mill (manufactured by IKA). s The powder is used as MXene powder.

[0167] Preparation of dispersion

[0168] The MXene powder (Ti3C2T s9.5 g of MXene powder) and 18 g of N-methylpyrrolidone (NMP) were stirred in a rotary mixer, and 4 g of NMP was added during the stirring, and further stirred until a substantially uniform MXene-NMP dispersion was obtained.

[0169] ·Coating of dispersion onto metal substrate

[0170] The MXene-NMP dispersion prepared above was applied to the upper surface of an aluminum foil (manufactured by THANK METAL CO., LTD., thickness 10 μm) as a metal substrate using a table-top coater.

[0171] Heat treatment

[0172] The aluminum foil coated with the MXene-NMP dispersion was preheated on a hot plate (80°C, 10 minutes), and then heat treated at 100°C for 10 hours in a vacuum oven (vacuum degree 0.1 kPa). Thus, a structure having a MXene dry film (hereinafter referred to as "NMP-MXene film") from the NMP dispersion formed on the upper surface of the aluminum foil as a conductive film was obtained.

[0173] ·suppress

[0174] Thereafter, the structure obtained above was pressed using a roll press at a line pressure of 0.6 kN / cm and a conveying speed of 0.3 m / min.

[0175] In this way, the conductive composite structure of Example 3 was obtained.

[0176] ·evaluate

[0177] The conductive composite structure of Example 3 prepared above was subjected to the same winding test, acetone immersion test and tape peeling test as in Example 1 and evaluated. The results of the winding test are shown in FIG. Figure 5 As shown in (a), no cracks in the NMP-MXene film and no peeling of the NMP-MXene film from the aluminum foil were observed. Figure 5 As shown in (b), the NMP-MXene film maintained its original shape, and no peeling between the NMP-MXene film and the aluminum foil was observed. Figure 5 As shown in (c), the NMP-MXene film was not peeled off from the aluminum foil by the tape at all.

[0178] (Example 4)

[0179] This embodiment relates to an example of producing a conductive composite structure using methyl ethyl ketone (MEK) as a reactive organic compound and aluminum foil as a metal substrate.

[0180] Preparation of MXene powder

[0181] Ti3C2T was obtained in the same manner as in Example 3. s The powder is used as MXene powder.

[0182] Preparation of dispersion

[0183] The MXene powder (Ti3C2T s 5.8 g of MXene powder) and 13.5 g of methyl ethyl ketone (MEK) were stirred in a rotary mixer, and 1.8 g of MXene powder and 4.3 g of distilled water were added during the stirring and further stirred. Stirring was performed until a substantially uniform MXene-MEK dispersion was obtained.

[0184] ·Coating of dispersion onto metal substrate

[0185] The MXene-MEK dispersion prepared above was applied to the upper surface of an aluminum foil (manufactured by THANK METAL CO., LTD., thickness 10 μm) as a metal substrate using a table-top coater.

[0186] Heat treatment

[0187] The aluminum foil coated with the MXene-MEK dispersion was preheated on a hot plate (80°C, 10 minutes), and then heat treated at 100°C for 10 hours in a vacuum oven (vacuum degree 0.1 kPa). Thus, a structure having a MXene dry film from the MEK dispersion (hereinafter referred to as "MEK-MXene film") formed on the upper surface of the aluminum foil as a conductive film was obtained.

[0188] ·suppress

[0189] Thereafter, the structure obtained above was pressed using a roll press at a line pressure of 0.6 kN / cm and a conveying speed of 0.3 m / min.

[0190] In this way, the conductive composite structure of Example 4 was obtained.

[0191] ·evaluate

[0192] The conductive composite structure of Example 4 prepared above was subjected to the same winding test, acetone immersion test and tape peeling test as in Example 1 and evaluated. The results of the winding test are shown in FIG. Figure 6 As shown in (a), no cracks in the MEK-MXene film and no peeling of the MEK-MXene film from the aluminum foil were observed. Figure 6As shown in (b), the MEK-MXene film maintained its original shape, and no peeling was observed between the MEK-MXene film and the aluminum foil. Figure 6 As shown in (c), in the case of the IPA-MXene film, only about 20% of the total area of ​​the adhered region was peeled off from the aluminum foil by the tape.

[0193] (Comparative Example 1)

[0194] This comparative example relates to an example in which a conductive composite structure is produced by using aluminum foil as a metal substrate without using a reactive organic compound.

[0195] Preparation of MXene clay

[0196] Ti3AlC2 particles were prepared as MAX particles using a known method. 1 g of the Ti3AlC2 particles (powder) was weighed, added to 10 mL of 9 mol / L hydrochloric acid together with 1 g of LiF and stirred at 35°C with a stirrer for 24 hours to obtain a solid-liquid mixture (suspension) containing solid components from the Ti3AlC2 powder. The solid-liquid mixture was washed with pure water and separated and removed by decantation using a centrifuge (the remaining sediment after the supernatant was removed was washed again) about 10 times to obtain a clay-like substance (clay) in the form of a sediment. Thus, Ti3C2T s - Aqueous dispersion clay as MXene clay.

[0197] Preparation of dispersion

[0198] The MXene clay (Ti3C2T s -water dispersion clay) was stirred using a thin film rotary high-speed stirrer (manufactured by Prymix Co., Ltd., 40-L type), and MXene powder (Ti3C2T s The mixture was stirred until a substantially uniform MXene-water dispersion was obtained.

[0199] ·Coating, heat treatment and pressing of dispersion onto metal substrate

[0200] The same procedures as in Example 3 were followed, except that the MXene-water dispersion prepared above was used instead of the MXene-MEK dispersion, and the dispersion was applied to the aluminum foil, and heat-treated and pressed.

[0201] In this way, the conductive composite structure of Comparative Example 1 was obtained.

[0202] ·evaluate

[0203] The conductive composite structure of Comparative Example 1 prepared above was subjected to the same winding test, acetone immersion test and tape peeling test as in Example 1 and evaluated. The results of the winding test are shown in FIG. Figure 7 As shown in (a), cracks were observed in the water-MXene film, and the water-MXene film peeled off from the aluminum foil and could not withstand bending. Figure 7 As shown in (b), no peeling between the water-MXene film and the aluminum foil was observed. Figure 7 As shown in (c), the water-MXene film is peeled off from the aluminum foil by a large area portion greater than about 70% of the adhesive area of ​​the tape, and the bonding force between the water-MXene film and the aluminum foil is low.

[0204] (Comparative Example 2)

[0205] This comparative example relates to an example in which dimethyl ether (DME) is used as the organic compound and aluminum foil is used as the metal substrate.

[0206] Preparation of MXene powder

[0207] Ti3C2T was obtained in the same manner as in Example 3. s The powder is used as MXene powder.

[0208] Preparation of dispersion

[0209] The MXene powder (Ti3C2T s 5.8 g of MXene powder (powder) and 13.5 g of dimethyl ether (DME) were stirred using a rotary-revolution stirrer, and 1.8 g of MXene powder and 4.3 g of distilled water were added during the stirring and further stirred. In these mixtures, lumps were formed and a substantially uniform dispersion could not be prepared, and a MXene-DME mixture containing lumps was obtained.

[0210] ·Coating of dispersion onto metal substrate

[0211] The MXene-DME mixture obtained above was attempted to be applied to the upper surface of an aluminum foil (manufactured by THANK METAL Co., Ltd., thickness 10 μm) as a metal substrate using a tabletop coater. However, it was difficult to apply the MXene-DME mixture. In addition, the mixture peeled off from the aluminum foil after application.

[0212] Therefore, in this Comparative Example 2, the test was stopped at the point in time when the MXene-DME mixture peeled off from the aluminum foil (no longer adhered), and a conductive composite structure could not be produced.

[0213] Industrial Applicability

[0214] The conductive composite structure of the present invention can be used in any appropriate application, but can be preferably used in applications requiring miniaturization and / or resistance to bending and stretching, and can be particularly preferably used as an electrode, for example.

[0215] This application claims priority based on Japanese Patent Application No. 2019-233667 filed in Japan on December 25, 2019, the entire contents of which are incorporated herein by reference.

[0216] Description of Reference Numerals

[0217] 1a, 1b, 1c layer main body (M m X n layer)

[0218] 3a, 5a, 3b, 5b, 3c, 5c Modified or terminal T

[0219] 7a, 7b, 7c MXene layer

[0220] 10 MXene (layered material)

[0221] 11 Metal substrate

[0222] 13 Conductive film

[0223] 20 Conductive composite structure

Claims

1. A conductive composite structure, The invention comprises a metal substrate and a conductive film provided on the surface of the metal substrate. The conductive film comprises a layered material, wherein the layered material comprises one or more layers, The layer comprises a layer body represented by the following formula and a modification or terminal T present on the surface of the layer body, wherein T is a hydroxyl group, an oxygen atom or a combination thereof, MmX n Wherein, M is at least one metal of Group 3, 4, 5, 6, or 7, X is a carbon atom, a nitrogen atom or a combination thereof, n is greater than or equal to 1 and less than or equal to 4, m is greater than n and less than 5, The surface of the metal substrate and the surface of the layer body are respectively bonded with residues derived from an organic compound having 2 to 8 carbon atoms and having a hydroxyl group, a carbonyl group or a combination thereof, wherein the organic compound is an alcohol or / and a ketone having 2 to 8 carbon atoms.

2. The conductive composite structure according to claim 1, wherein The organic compound includes at least one selected from the group consisting of isopropyl alcohol, N-methylpyrrolidone, and methyl ethyl ketone.

3. The conductive composite structure according to claim 1 or 2, wherein: The metal substrate has a sheet-like morphology.

4. The conductive composite structure according to claim 1 or 2, wherein: The metal substrate is an aluminum substrate, a copper substrate or a stainless steel substrate. The conductive composite structure according to claim 1 or 2, which is used as an electrode.

6. The conductive composite structure according to claim 1 or 2, wherein: The conductive composite structure satisfies the following (1) and (2): (1) As a core winding test, the conductive composite structure was wound around an aluminum round bar with a diameter of 4 mm for about 2 turns. When this state was maintained and visually confirmed, no cracks in the conductive film and no peeling of the conductive film from the metal substrate were observed; (2) As a tape peeling test, a transparent adhesive tape is affixed to a portion of the upper surface of the conductive film of the conductive composite structure, which is then peeled off and visually confirmed that the total area of ​​the conductive film peeled off by the tape is less than 20% of the area of ​​the conductive film to which the tape was affixed.

7. A method for producing a conductive composite structure comprising a metal substrate and a conductive film disposed on a surface of the metal substrate, comprising: (a) preparing a dispersion in which a layered material is dispersed in a liquid medium containing an organic compound having a carbon number of 2 or more and 8 or less and having a hydroxyl group, a carbonyl group or a combination thereof, wherein the layered material is a layered material including one or more layers, and the organic compound is an alcohol or / and a ketone having a carbon number of 2 or more and 8 or less, The layer comprises a layer body represented by the following formula and a modification or terminal T present on the surface of the layer body, wherein T is a hydroxyl group, an oxygen atom or a combination thereof, M m X n Wherein, M is at least one metal of Group 3, 4, 5, 6, or 7, X is a carbon atom, a nitrogen atom or a combination thereof, n is greater than or equal to 1 and less than or equal to 4, m is greater than n and less than 5; (b) applying the dispersion to the surface of a metal substrate; and (c) subjecting the metal substrate to which the dispersion has been applied to heat treatment.

8. The manufacturing method according to claim 7, wherein: The heat treatment is performed at a temperature of 70° C. to 200° C. both inclusive.

9. The manufacturing method according to claim 7 or 8, wherein: The organic compound includes at least one selected from the group consisting of isopropyl alcohol, N-methylpyrrolidone, and methyl ethyl ketone.

10. The manufacturing method according to claim 7 or 8, wherein: The metal substrate has a flake-like morphology.

11. The manufacturing method according to claim 7 or 8, wherein: The metal substrate is an aluminum substrate, a copper substrate or a stainless steel substrate.